Solve the following system of equations. 2x + y = 3 x = 2y - 1 Make sure there are NO SPACES in your answer. Include a comma in your answer. ANSWER: {( a0 )}

Respuesta :

Answer:  [tex]x=1;y=1[/tex] or (1,1)

Step-by-step explanation:

You can apply the Method of substitution.

Knowing that  [tex]x = 2y - 1[/tex] (second equation), you can substitute it into the first equation and solve for the variable y:

[tex]2x+y=3\\2(2y - 1)+y=3\\4y-2+y=3\\5y=3+2\\5y=5\\y=1[/tex]

Now you need to substitute [tex]y=1[/tex] into the second equation [tex]x = 2y - 1[/tex] to calculate the value of the variable x. Then:

[tex]x = 2(1) - 1\\x=2-1\\x=1[/tex]

Then, the solution is:

[tex]x=1;y=1[/tex] or (1,1)

Answer: your solution would be (1,1)

Step-by-step explanation:

ACCESS MORE